2022
DOI: 10.3389/fgene.2022.800019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of WRKY Gene Family in Response to Abiotic Stress in Dendrobium catenatum

Abstract: Dendrobium catenatum has become a rare and endangered medicinal plant due to habitat loss in China. As one of the most important and largest transcription factors, WRKY plays a critical role in response to abiotic stresses in plants. However, little is known regarding the functions of the WRKY family in D. catenatum. In this study, a total of 62 WRKY genes were identified from the D. catenatum genome. Phylogenetic analysis revealed that DcWRKY proteins could be divided into three groups, a division supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Investigating the expression patterns of genes in various tissues is of paramount importance for mining functional genes ( Dutta et al., 2018 ). Research has demonstrated that WRKY genes exhibit expression in one or more tissues, and they are crucial for plant growth and development ( Feng et al., 2022 ; Zhang et al., 2022b ). The evolutionary relationship between CsWRKY7 and AtWRKY7 in Camellia sinensis is closely related, and root elongation was higher in CsWRKY7 than in wild type ( Chen et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the expression patterns of genes in various tissues is of paramount importance for mining functional genes ( Dutta et al., 2018 ). Research has demonstrated that WRKY genes exhibit expression in one or more tissues, and they are crucial for plant growth and development ( Feng et al., 2022 ; Zhang et al., 2022b ). The evolutionary relationship between CsWRKY7 and AtWRKY7 in Camellia sinensis is closely related, and root elongation was higher in CsWRKY7 than in wild type ( Chen et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Group III WRKY genes are considered the most vital group in gene family evolution and seemingly play an important role in the adaptation and evolution of plants ( Zhang and Wang, 2005 ; Goel et al, 2016 ; Shan et al, 2021 ; Khan et al, 2022 ). In C. sinense , 11 CsWRKY gene members belonged to Group III, and such a number is fewer than the corresponding number in most other plants, such as 13 in Arabidopsis ( Kalde et al, 2003 ), 28 in rice ( Wang et al, 2015 ), 35 in maize ( Hu et al, 2021 ), 62 in Dendrobium catenatum ( Zhang et al, 2022b ), 57 in Phalaenopsis , and 43 in Apostasia (unpublished). These findings suggested the functional conservation of WRKY genes during orchid evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the regulatory mechanisms of GmWRKYs, 32 types of cis-elements were identi ed in the promoters of GmWRKYs [49,50], which were involved in hormone responses, stress responses, plant growth, and developmental response, and light responses (Fig. 4 and Table S6).…”
Section: Promoter Analysis Of Gmwrky Genesmentioning
confidence: 99%